An examination of the multi-campus university in the context of the peripheral innovation system : a case of the University of Costa Rica - Rojas Calvo, Sebastián José 1982- (2023)
Universities play an important role in strengthening the innovation capabilities of the regions in which they are situated, through their ability to generate new knowledge and interact with regional actors to diffuse their knowledge. Studies have demonstrated the existence of gaps between central and peripheral regions related to the concentration of resources and institutional density, placing peripheral regions at a clear disadvantage due to their reduced ability to generate sufficient critical mass to sustain the dynamism and inertia necessary to innovate. Universities can play a key role in working with peripheral regions, particularly through their activities within the third mission, to reduce this gap and increase innovative capabilities. However, their ability to achieve this can be limited by a concentration in central regions. Multi-campus universities present one potential solution to this problem, where satellite campuses of a centrally located university are positioned in peripheral regions to undertake activities appropriate to that region's individual requirements, especially peripheral regions. However, the limited research examining multi-campus universities results in a lack of understanding of the activities performed by satellite campuses, collaboration within the multi-campus system, and the barriers and enablers to their third mission activities. This study investigates the multi-campus phenomenon to address the above gaps in the literature. The research consists of three main phases. First, a systematic literature review phase is undertaken to establish the roles belonging to the third mission from the perspective of regional innovation systems, along with the enablers and barriers that affect these roles. Second, an exploratory phase explores the interactions between senior and satellites, and between subsystems of generation and exploitation of knowledge, through the application of interviews with coordinators, and directors...